Pengaruh Kualitas Produk, Harga, Dan Promosi Sebagai Penentu Keputusan Pembelian Pada Pelanggan Stars Collections - Setiyawan, Muhammad Ilham Ardi; Pardiman, Pardiman; Amin, Muhammad Sirojuddin (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This research wants to explore how product quality, price, and promotion influence the purchasing decisions of Stars Collections cutomers. The population in this study was Stars Collections consumer, with a sample of 85 respondent selected using a accidental sampling technique. Data collection methods used a questionnaire, while data analysis employed multiple linier regressions analysis. The results from this study reveal that, on an individual basis, product quality plays a key role in influencing purchase decisions, much like price does, whereas promotion doesn't make a difference. However, when you look at them all at once, product quality, price, and promotion combined do have a notable impact on how customers of Stars Collections decide to buy. Keywords: Product Quality, Price, And Promotion